Baseline characterization of sediments and marine biota near industrial effluent discharge in Northumberland Strait, Nova Scotia, Canada. (August 2020) - Chaudhary, Meenakshi; Walker, Tony R.; Willis, Rob; Oakes, Ken
Abstract: A bleached kraft pulp mill operating in Nova Scotia, Canada has discharged effluent into a former tidal estuary known as Boat Harbour since 1967. After treatment in Boat Harbour, effluent is discharged into Northumberland Strait. Contaminated sediments in Boat Harbour are slated for remediation following cessation of effluent discharge. A review of historical documents to identify contaminants in marine biota in Northumberland Strait found insufficient data to properly assess baseline conditions prior to remediation. This study measured metal, methylmercury, dioxin and furan concentrations in surficial sediments and American lobster ( Homarus americanus ), rock crabs ( Cancer irroratus ) and blue mussels ( Mytilus edulis ) in Northumberland Strait. When compared to Canadian Council of Ministers of the Environment sediment quality guidelines and Canadian Food Inspection Agency tissue guidelines results indicated limited contamination in sediments and biota, posing low risk to marine biota. Long-term monitoring is recommended to verify effectiveness of remediation. Graphical abstract: Unlabelled Image Highlights: Contaminated sediments from pulp mill effluents will be remediated in a coastal freshwater lagoon. Baseline studies to characterize downgradient marine sediments and biota before remediation are lacking. Contaminants in marine sediments, blue mussels, American lobster and rock crabs were analyzed. Sediment metal, total mercury, dioxin and furan concentrations were below Canadian ISQG guidelines and PELss. Methylmercury concentrations in lobster and rock crabs exceeded Canadian tissue residue guidelines.